2015
DOI: 10.1159/000371854
|View full text |Cite|
|
Sign up to set email alerts
|

Submandibular Gland Transfer for the Prevention of Postradiation Xerostomia in Patients with Head and Neck Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: Submandibular gland transfer has been widely used to prevent postradiation xerostomia in head-and-neck cancers. However, there are still some controversies. Methods: Six databases were searched, data extraction was performed and the risk of bias was assessed by 2 reviewers independently. The meta-analysis was performed using Review Manager, version 5.2. Results: A total of 7 trials (12 articles) and 369 participants were included. Conclusions: The present clinical evidence suggests that submandibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…The risk of bias assessment form recommended by Saltaji et al [14] and Wu et al [15] was used to evaluate the risk of bias of included studies. This assessment system evaluated the risk of bias on the basis of four broad perspectives: study design (8 items), study measurements (3 items), statistical analysis (3 items) and baseline information (1 item), with a maximum score of 19. the item was scored as 1 point (√) when the trial reported the domain properly, as 0.5 point (≠) when the trial partially fulfilled the criteria and as 0 point (×) when the trial did not fulfill the methodological criteria (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias assessment form recommended by Saltaji et al [14] and Wu et al [15] was used to evaluate the risk of bias of included studies. This assessment system evaluated the risk of bias on the basis of four broad perspectives: study design (8 items), study measurements (3 items), statistical analysis (3 items) and baseline information (1 item), with a maximum score of 19. the item was scored as 1 point (√) when the trial reported the domain properly, as 0.5 point (≠) when the trial partially fulfilled the criteria and as 0 point (×) when the trial did not fulfill the methodological criteria (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This assessment system evaluated the risk of bias on the basis of four broad perspectives: study design (8 items), study measurements (3 items), statistical analysis (3 items) and baseline information (1 item), with a maximum score of 19. the item was scored as 1 point (√) when the trial reported the domain properly, as 0.5 point (≠) when the trial partially fulfilled the criteria and as 0 point (×) when the trial did not fulfill the methodological criteria (Table 1). The study was assessed as ‘low risk of bias’ when the score was higher than 15, ‘moderate risk of bias’ when the score was between 10 and 15, and ‘high risk of bias’ when the score was less than 10 points [14, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, patients undergoing the SGT showed better swallowing outcomes without any surgical complications associated with the procedure . These findings were further supported by multiple systematic reviews and meta‐analyses that concluded SGT is highly effective in preventing the incidence of xerostomia in patients receiving RT …”
Section: Introductionmentioning
confidence: 57%
“…11,12,14,15 These findings were further supported by multiple systematic reviews and meta-analyses that concluded SGT is highly effective in preventing the incidence of xerostomia in patients receiving RT. 16,17 The classical SGT is, however, only indicated in patients with primary cancers in which the submental area is spared by the radiation field during treatment (larynx, oropharynx, hypopharynx, skin, or unknown primaries). Unfortunately, its use is contraindicated in oral cavity primaries because the submental area cannot be effectively or safely shielded from radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In patients treated through chemotherapy and radiotherapy, amifostine prevented chronic xerostomia, but it was not effective on acute xerostomia [51]. The side effects that patients using amifostine can present during oncologic treatment are arterial hypotension, nausea, vomits, asthenia, fever, mucositis, tachycardia, bronchitis, allergic reaction and rash [33,52,53]. The higher the applied dose, the more severe the side effects related to amifostine.…”
Section: -70gy≥40gy In Parotid Glands ≥40gy In Submandibular Glandsmentioning
confidence: 99%